Reinventing a Folk Hero in Yashar Kemal’s Epic Novel, Memed, My Hawk - HASHEMIPOUR, Saman; ., . (International Journal of Engineering and Technology, 2018)
A millennium after the Day of Ashura, Yashar Kemal’s folk hero, Memed, rises against another atrocious dynastic ruler. Husayn Ibn Ali, the grandson of Muhammad, the prophet of Islam, was killed and beheaded in the Battle of Karbala in 680 AD to end a caliphate, taking full account of claiming his life. Annually, Shiite and Alevi Muslims hold funeral ceremonies worldwide for his martyrdom on certain days to remember their liberty, as Memed’s compatriots, the villagers of Değirmenoluk in Yashar Kemal’s epic masterpiece, Memed, My Hawk do. Heroes do not accept injustice, but right all wrongs at all costs. Die or live as a hero, people compose ballads of protagonist’s heroism and consider their liberators as holy figures.